A modified S-iteration process for G-nonexpansive mappings in Banach spaces with graphs - Raweerote Suparatulatorn (2018)
© 2017, Springer Science+Business Media New York. In this work, we prove the weak and strong convergence of a sequence generated by a modified S-iteration process for finding a common fixed point of two G-nonexpansive mappings in a uniformly convex Banach space with a directed graph. We also give some numerical examples for supporting our main theorem and compare convergence rate between the studied iteration and the Ishikawa iteration.